Factors associated with depression among women living with HIV in Bangui, Central African Republic - Ngouyombo, Ange Donatien; Simaléko Mbéko, Marcel; Woromogo, Sylvain Honoré; Garoua-Adjou, Stéphanie Inesse; Honisse, Hortence; Longo, Jean de Dieu; Grésenguet, Gérard (International Journal Of Community Medicine And Public Health, 2025)
Background: Depressive disorders significantly affect the well-being and quality of life of people living with HIV, particularly women. This study investigated the extent of mental health issues among women living with HIV in Bangui and analyzes associated factors. Methods: A cross-sectional analytical study was conducted from January 1 to November 30, 2024, involving HIV-positive women at the National Reference Center for Sexually Transmitted Infections and Antiretroviral Therapy in Bangui. Depression was assessed using the Beck Depression Inventory and a second questionnaire was used to assess the determinants of mental health. Univariate and multivariate analyses identified factors associated with depression, while controlling for potential confounding effects. Results: A total of 570 women living with HIV were recorded during the study period. Their ages ranged from 18-63 years, with an average of 31 years (±6). The prevalence of depression among HIV-positive women in Bangui was estimated to be 54.7%. Having multiple children to care for (OR=1.93, 95% CI- 1.30-2.85, p=0.012), absence of income-generating activity (OR=2.18; 95% CI- 1.60-2.98, p=0.001), psychological pressure from the environment (OR=2.03, 95% CI- 1.14-4.18; p=0.003), the experience of stress (OR=3.47; 95% CI- 2.11-5.99; p<0.001) and being abandoned by a partner were the main factors associated with depression ( OR=2.94; 95% CI- 1.10-7.85; p=0.012). Conclusions: Depression is highly prevalent among HIV-positive women in Bangui. Early detection and integrated psychosocial support are essential to address this public health concern.